Functional characterization of host toxic EcdB transcription factor protein of echinocandin B biosynthetic gene cluster. (10th July 2019) - Kumar, Arvind; Kumar, Vinay; Kumar, Antresh
Abstract: The ecdB is a transcription factor, located in the echinocandin B biosynthetic gene cluster of Emericella rugulosa NRRL11440. Here, we validated the ecdB mRNA sequence for functional expression and to explore the role of EcdB protein in the echinocandin B regulation. The sequence alignment study revealed that the ecdB coding sequence was found 75 bp shorter than the reference mRNA sequence. This coding sequence encodes for EcdB protein and comprises three conserved domains; DNA binding domain (DBD), coiled‐coil domain, and signature middle homology region. The full‐length and DBD (truncated) DNA sequences were expressed in Escherichia coli BL21(DE3) under different tested conditions. The expression of EcdB protein was found to be toxic, which curbs the cell growth. In contrast to truncated protein (GST:EcdB1‐54), the full‐length (GST:EcdB) protein was expressed at very low titer and not detectable in SDS‐PAGE under the varying isopropyl β‐d ‐1‐thiogalactopyranoside (IPTG), temperature, and media conditions. However, GST:EcdB1‐54 was successfully purified under standard conditions (0.5 mM IPTG at 0.5OD) with 33 kDa expected size. The functionality of GST:EcdB1‐54 was attained by electrophoretic mobility shift assay study as a clear band shifting showed with ecdA promoter. Taken together, we conclude that EcdB interacts with the ecdA promoter that reflected to require for echinocandin B regulation.